1996
DOI: 10.1073/pnas.93.26.15221
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule reorganization is obligatory for growth cone turning

Abstract: To examine the role of microtubules in growth cone turning, we have compared the microtubule organization in growth cones advancing on uniform laminin substrates with their organization in growth cones turning at a laminin-tenascin border. The majority (82%) of growth cones on laminin had a symmetrical microtubule organization, in which the microtubules entering the growth cone splay out toward the periphery of the growth cone. Growth cones at tenascin borders had symmetrically arranged microtubules in only 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 60 publications
8
93
0
Order By: Relevance
“…We found that branching from the growth cone and the axon shaft is always preceded by splaying apart of looped or bundled microtubules which is accompanied by localized accumulation of F-actin. Dynamic microtubules colocalize with F-actin in transition regions of growth cones and axon branch points, consistent with observations in fixed growth cones (Bridgman and Dailey, 1989;Challacombe et al, 1996Challacombe et al, , 1997Williamson et al, 1996;Rochlin et al, 1999), whereas F-actin is excluded from regions of stable microtubules (Fig. 9).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We found that branching from the growth cone and the axon shaft is always preceded by splaying apart of looped or bundled microtubules which is accompanied by localized accumulation of F-actin. Dynamic microtubules colocalize with F-actin in transition regions of growth cones and axon branch points, consistent with observations in fixed growth cones (Bridgman and Dailey, 1989;Challacombe et al, 1996Challacombe et al, , 1997Williamson et al, 1996;Rochlin et al, 1999), whereas F-actin is excluded from regions of stable microtubules (Fig. 9).…”
Section: Discussionsupporting
confidence: 74%
“…Cultures were then mounted in 80% glycerol and PBS. To quantif y the distributions of tyrosinated and acetylated microtubules in relation to F-actin, cortical neuronal cultures were simultaneously extracted and fixed to preserve the majority of F-actin and microtubules but to extract cytoplasmic G-actin and tubulin (Challacombe et al, 1996;Williamson et al, 1996). This microtubule-F-actin fixative was composed of 4% paraformaldehyde, 0.25% glutaraldehyde (EM Sciences), 0.1% Triton X-100 (Sigma), 10 M taxol (Sigma), and 1.3 M phalloidin (Molecular Probes) in PH EM buffer (60 mM PI PES, 25 mM H EPES, 10 mM EGTA, and 2 mM MgC l 2 , pH 6.9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the observation that PC12 cells require tubulin polymerization and reorganization of the microtubule cytoskeleton for neurite outgrowth to occur (47)(48)(49)(50)(51). To investigate whether ENTH domains might also be able to influence tubulin polymerization, we examined for alterations in neurite outgrowth in PC12 cells expressing ENTH domains.…”
Section: Fig 5 Saturation Binding Analysis Of Enth Domain/tubulin Isupporting
confidence: 51%